1. Time and History: Biblical and Theological Studies 2. Is the Church Too Asian? Reflections on the Ecumenical Councils 3. Unity of Knowing and Acting in Kant 4. Hindu View of Life: A Contemporary Perspective - Chethimattam, John B; Kaipayil, Joseph; Thonippara, Francis; Kalluveettil, Paul (Journal of Dharma, 2003)
1.Joseph Pathrapankal, Time and History: Biblical and Theological Studies, Bangalore: Asian Trading Corporation, 2002, pages vi + 254. ISBN: 81-7086-287-6. 2. Norman Tanner, Is the Church Too Asian? Reflections on the Ecumenical Councils, Rome: Chavara Institute of Indian and Inter-Religious Studies, and Bangalore: Dharmaram Publications, 2002, pages vi + 92. ISBN: 81-86861-48-3. 3. Saju Chackalackal, Unity of Knowing and Acting in Kant, Bangalore: Dharmaram Publications, 2002, pages xx + 615. ISBN: 81-86861-51- 4. M. Sivaramkrishna, Hindu View of Life: A Contemporary Perspective, Bangalore: Dharmaram Publications, 2001, pages 184. ISBN: 81-86861-38-6.